Socket Preservation After Tooth Extraction Maxillary Lateral Incisor: A Case Report - Norman Hidajah; R.A Eka Yunanthi; Ketut Virtika Ayu; Surwandi Walianto (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
as a result off a tooth loss. These change are usually significant and can make placement of a conventional denture or an implant more difficult. Socket preservation after tooth extraction can minimize ridge resorption. Socket preservation can be done by atraumatic tooth extraction, placement of bone graft material, membrane combination of bone graft and membrane, and connective tissue graft. History and Clinical Findings: a 40 year old woman came to the clinic complaining of a fractured right upper front tooth 3 years ago due to an accident and wanted to make dentures. Intraoral examination did not reveal any remaining teeth in region 12. X-ray results revealed fractured root remnants in the socket. Case Treatment: The extraction procedure was carried out using the close method, giving bone graft and suturing. Conclusion: post extraction maintenance of the alveolar ridge minimizes residual ridge resorption and, thus, allows placement of a conventional denture or an implant that satisfies esthetic and functional criteria.